Preexisting musculoskeletal burden and its development under letrozole treatment in early breast cancer patients. Issue 8 (2nd April 2019) - Nabieva, Naiba; Häberle, Lothar; Brucker, Sara Y.; Janni, Wolfgang; Volz, Bernhard; Loehberg, Christian R.; Hartkopf, Andreas D.; Walter, Christina‐Barbara; Baake, Gerold; Fridman, Alexander; Malter, Wolfram; Wuerstlein, Rachel; et al.
Abstract : One of the most common adverse events (AEs) occurring during treatment with aromatase inhibitors (AIs) is musculoskeletal pain. The aim of our study was to analyze the influence of preexisting muscle/limb pain and joint pain on the development of AI‐induced musculoskeletal AEs. Women eligible for upfront adjuvant endocrine therapy with letrozole were included in the PreFace study, a multicenter phase IV trial. During the first treatment year, they were asked to record musculoskeletal AEs monthly by answering questions regarding pain symptoms and rating the pain intensity on a numeric rating scale from 0 (no pain) to 10 (very strong pain). Pain values were compared using nonparametric statistical tests. Overall, 1, 416 patients were evaluable. The average pain value over all time points in women with preexisting muscle/limb pain was 4.3 (median 4.3); in those without preexisting pain, it was 2.0 (median 1.7). In patients without preexisting muscle/limb pain, pain levels increased relatively strongly within the first 6 months (mean increase +0.9, p < 0.00001) in comparison with those with preexisting pain (mean increase +0.3, p < 0.001), resulting in a statistically significant difference ( p < 0.00001) between the two groups. The development of joint pain was similar in the two groups. Women without preexisting muscle/limb pain or joint pain have the greatest increase in pain after the start of adjuvant AI therapy. Women with preexisting pain have significantly higher pain values. The main increase in pain values takes place during the first 6 months of treatment. Abstract : What's new? A standard treatment for breast cancer is aromatase inhibitors (AIs), but common adverse events including musculoskeletal pain can cause early discontinuation. This study analyzed the influence of preexisting muscle/limb pain and joint pain on the development of AI‐induced musculoskeletal adverse events. Women without preexisting muscle/limb or joint pain have the greatest increase in pain after starting adjuvant AI therapy. Women with preexisting pain have higher pain scores, but a smaller increase in pain in comparison. The main increase in pain scores takes place in the first 6 months of endocrine treatment, calling for greater physician attention during this time window.